Effect of four-stage refinement with fortified measures to inhibit oil oxidation and purification on the quality of anchovy oil - Li Li Xu; Ya Nan Xu; Wei Jia Liu; Chang Hu Xue; Tong Cheng Xu; Yun Qi Wen (Food Chemistry: X)
Traditional refining processes of crude anchovy oil uses high temperatures. In order to inhibit oil oxidation, intensified measures should be taken. The impact of traditional four-stage refinement on anchovy oil quality have not yet been systematically revealed. This study proposed improved four-stage refining process to refine anchovy oil, and the improved methods could efficiently reduce the risk of oil oxidation. Deacidification could remove some kinds of heavy metal ions but not transition metal ions. Decolorization could remove large amounts of volatile compounds, but it could not effectively improve the sensory quality of oil while deodorization did. The refined efficiency of prior stage greatly influenced that of the latter process. After refinement, purification applying multiple adsorbents could further improve oil quality, but greatly decreased oil oxidation stability. This study provided a reference to the refinement of fish oil and develop progressive refining process inspired by the purification.